STUDY OF ANTIMICROBIAL ACTION OF ESSENTIAL OIL FROM STEMS OF ROSMARINUS OFFICINALIS L. (LAMIACEAE) - Z. M. Tohsirova; A. S. Nikitina; O. I. Popova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
The aim of this work was to investigate the antibacterial activities using the method of wells of Rosmarinus officinalis essential oil, introduced in the Botanical garden of PMPI. It is established that the essential oil has the most pronounced antibacterial activities against Staphylococcus aureus and Enterococcus faecalis, less - Escherichia coli and Candida albicans. Antimicrobial effect on the test-cultures of microorganisms Pseudamonas aeruginosa and Proteus vulgaris are not expressed.